The Influence of Organizational Commitment and Burnout to Employee Performance through Extra-Role Behavior as Intervening Variable in PT. Bank SulutGo Cabang Manado - Alfian Ranny Poluan; Heidy Pesik; Fresi Beatrix Lendo (Syntax Corporation Indonesia, 2024)
The purpose of this study is to analyze the structural relationship between organizational commitment, burnout, performance and extra-role behavior of employees. Design/methodology/approach – The research question is examined using a sample of PT. Bank SulutGo kantor cabang Manado employees. Path Analysis is used to test various research hypotheses and examine the extent of extra role behavior mediate the effect of organizational commitment and burnout on employee performance. Findings – First, there is a non-significant relationship between organizational commitment and burnout to extra role behavior. Second, there is a positive and significant relationship between organizational commitment and employee performance, while burnout has negative and non- significant relationship. Third, extra-role has positive and significant relationship to employee performance. Practical Implications – Based on this empirical finding should be concerned commitment to be used as a benchmark to improve employee performance. Besides that, it should be noted that for the banking sector extra-role behavior can be categorized as a work culture. Research Limitations – There is a need to extend the results and compare with other banking industries. Originality – This research explain that extra-role behavior contributes as a medium to the evaluation of organizational commitment and employee performance.